MENDIDIK AKHLAQ AL KARIMAH ANAK USIA DINI: KOLABORASI SEKOLAH DAN KELUARGA - Masganti Sit (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Akhlaq al Karimah is the best gift parents give to their children, therefore they always choose quality schools to help them educate, especially the noble character of their children. But various studies show that schools are not fully able to replace the position of parents as educators. Therefore, when school always cooperates with parents in parenting activities to jointly educate children's Akhlaq al Karimah. The purpose of the study was to obtain information about parents' dan school’s views on parenting activities carried out to equip them to educate their children's noble character at home. This research was conducted on 10 parents of RA An Nida students. Collecting data using observation and interviews with qualitative data analysis. The results showed that parents have a positive view of parenting activities carried out by schools that help them educate their children's Akhlaq al Karimah at home.